2015
DOI: 10.1055/s-0034-1396768
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Elbow Replacement Arthroplasty

Abstract: Elbow replacement arthroplasty has become a standard surgical treatment for a variety of diseases of the elbow. First popularized for the treatment of late-stage rheumatoid arthritis and other debilitating forms of joint disease, the current indications have expanded to include primary treatment of elbow trauma. The most commonly used total elbow replacements are linked semiconstrained chromium-molybdenum alloy or titanium alloy prostheses with polyethylene bearing surfaces. These are inserted after resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This forgiving design reduces hardware loosening, although it comes at the expense of increased polyethylene wear. 5 Heijink et al, in an analysis of 30 articles from 1940 to 2015, found no evidence to support one type of radial head prosthesis over another. 50 Radial head replacement is performed most frequently in the context of trauma and has shown favorable outcomes regarding the restoration or prevention of instability and range of motion.…”
Section: Radial Head Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…This forgiving design reduces hardware loosening, although it comes at the expense of increased polyethylene wear. 5 Heijink et al, in an analysis of 30 articles from 1940 to 2015, found no evidence to support one type of radial head prosthesis over another. 50 Radial head replacement is performed most frequently in the context of trauma and has shown favorable outcomes regarding the restoration or prevention of instability and range of motion.…”
Section: Radial Head Arthroplastymentioning
confidence: 99%
“…5,11 They are composed of chromiummolybdenum alloy or titanium alloy humeral and ulnar stems that are linked by a polyethylene bearing surface. 5 The bushing is composed of two polyethylene liners and placed between the metal components that are then linked via a transverse pin. A Cring holds the pin in place.…”
mentioning
confidence: 99%
“…Our search identified 13 studies reporting on the diagnosis of PEI. [3][4][5]8,29,31,[36][37][38][39][40][41][42] This included two current concepts reviews, eight retrospective case series or cohort studies, two diagnostic studies and one clinical practice guideline.…”
Section: Diagnosismentioning
confidence: 99%
“…4,29,36 Some authors have suggested that early progressive lucency and endosteal scalloping are characteristic of PEI. 5,29,42 Gille et al 8 reported that four of the six elbows in their series that underwent single-stage revision for infection had evidence of radiolucency on imaging. Further imaging in the form of bone scanning, leucocyte scans, CT, MR or PET is not currently recommended by the Infectious Diseases Society of America guidelines.…”
Section: Diagnosismentioning
confidence: 99%